FRANCIS BACON (1909-1992): PHOTOGRAPHS AND PAINTING, FROM LONDON TO DUBLIN - Eleonora Jedlińska (Zbornik radova Filozofskog fakulteta u Splitu, 2021)
Francis Bacon painted pictures based mostly on photographs published in encyclopaedias, popular magazines, the tabloid press, posters and packaging. He was interested in reproductions of paintings by great masters. He used photographs by Muybridge. Photographs, treated by Bacon as tools, were later “worked on” by the artist, becoming the canvas for his paintings. The scenes he chose – often drastic, depicting rape and violence – were painted into his canvases, creating a deformed image of the world that “emerged” from the horrors of both world wars. He painted portraits based on his photographs of friends. These were usually people with whom the artist was emotionally connected. He painted self-portraits base on a series of photographs taken in automatic photography, from which he selected several to form the basis of his paintings. Real things and persons should exist in the fictional space assigned to them. By destroying literalism in painting, Bacon wanted to find the similarity desired in painting as its principal, so to rediscover realism. When painting a portrait, he tried to capture the appearance of the figure. After Francis Bacon’s death, his London studio (7, Reece Mews), restored by conservators, was “repeated” in the space of the Hugh Lane Gallery in Dublin. It contains about 7,500 objects, among them numerous photographs which had been torn up by the artist, photographs of his lovers and friends, black and white reproductions. The Bacon ‘archive’ collected in Dublin is now a silent hint of the creative process of the artist, who despite numerous studies devoted to him and recorded conversations, still remains one of the most inscrutable artists of the 20th century.